The multicultural e-comics: innovative media to improve elementary school students' social studies learning achievement - Yuni Suprapto; Popi Monika; Putri Rachmadyanti; Sugiantoro Sugiantoro; Ferani Mulianingsih; Abdul Ghofur (Jurnal Ilmiah Pendidikan Dasar, 2026)
In the form of a multicultural-based educational e-comic, to improve the learning achievement of fourth-grade IPAS students at Kaliwadas 01 State Elementary School. This type of research is Research and Development (R&D), which was developed referring to the 4D development stage; the e-comic learning media developed is feasible to be applied in learning. The subjects in this study were fourth-grade students at Kaliwadas 01 State Elementary School. The data sources in this study were primary data and secondary data. Data collection techniques used interviews, observations, tests, questionnaires, and documentation. Data analysis techniques used were interview data analysis, expert validation assessment questionnaire data, and student responses. The results of the study obtained that multicultural-based educational e-comic media is feasible and valid to use, based on the results of media validation by media experts getting 80% in the “good” category and material experts getting 81.1% in the “good” category, and the assessment given by students getting 90% in the “good” category. The development of multicultural-based educational e-comic media is feasible to use in learning, and the results of understanding the overall score for the pretest of 940 and post-test of 1650, while the average pretest score is 47 and the average post-test score is 82.5. So it can be concluded that there is an increase in students' understanding of IPAS subjects related to the material of Indonesia, which is rich in culture using multicultural-based educational e-comic media.